2014
DOI: 10.2215/cjn.00360114
|View full text |Cite|
|
Sign up to set email alerts
|

Nephrotoxic Effects of Common and Emerging Drugs of Abuse

Abstract: The kidneys can be injured in diverse ways by many drugs, both legal and illegal. Novel associations and descriptions of nephrotoxic effects of common and emerging drugs of abuse have appeared over the past several years. Anabolic androgenic steroids, illicitly used by athletes and others for decades to increase muscle mass and decrease body fat, are emerging as podocyte toxins given recent descriptions of severe forms of FSGS in long-term abusers. Synthetic cannabinoids, a new group of compounds with marijuan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
84
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(94 citation statements)
references
References 84 publications
3
84
0
7
Order By: Relevance
“…Two recent reviews of nephrotoxicity from illicit drugs have found some evidence of direct nephrotoxicity. Where kidney biopsies have been available, renal injury other than acute tubular necrosis have included acute interstitial nephritis and glomerulonephritis as the commonest, but other findings include thrombotic microangiopathy (MDMA), vasculitis (MDMA, cocaine), vascular thrombosis or infarction (cocaine), and crystal nephropathy (heroin, cannabinoids) . The additional mechanisms of renal injury may explain why illicit drug users develop worse AKI even allowing for their higher CK.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent reviews of nephrotoxicity from illicit drugs have found some evidence of direct nephrotoxicity. Where kidney biopsies have been available, renal injury other than acute tubular necrosis have included acute interstitial nephritis and glomerulonephritis as the commonest, but other findings include thrombotic microangiopathy (MDMA), vasculitis (MDMA, cocaine), vascular thrombosis or infarction (cocaine), and crystal nephropathy (heroin, cannabinoids) . The additional mechanisms of renal injury may explain why illicit drug users develop worse AKI even allowing for their higher CK.…”
Section: Discussionmentioning
confidence: 99%
“…First is Valsalva maneuvers during inhalation of the drug and second is CHS with recurrent vomiting. Due to the relative short duration of K2 and normal lung parenchyma, it is unlikely that the patient had a direct pulmonary insult leading to barotrauma [34].…”
Section: Discussionmentioning
confidence: 99%
“…Drug users can present with a wide variety of kidney involvement, including glomerular, vascular, and tubulointerstitial, which could be related to either direct or indirect nephrotoxic effects of the drug in question (Table 1). 1,2 Although the kidney complications from certain drugs (eg, cocaine) are well known, the spectrum of kidney complications from recreational drugs remain elusive due to the emergence of new agents such as synthetic cannabinoids, as well as the dynamic pattern of drug use.…”
Section: Discussionmentioning
confidence: 99%